Assessing Urban Surface Runoff Management Using the SWAT Model, GIS, and the Rational Method: A Case Study of Karapakkam - Yogashri I; N. Sudhan Srinivas (International Journal of Environmental Planning and Development Architecture, 2026)
Urban surface runoff management encompasses strategies aimed at regulating rainwater flow, reducing urban flooding, enhancing groundwater recharge, and contributing to disaster risk mitigation for sustainable urban development. This study seeks to optimize surface runoff management in urban settings by using the soil and water assessment tool (SWAT) model integrated with geographic information systems (GIS) to minimize flood risks. The research focuses on the peak runoff in Karapakkam, a locality within the Chennai Metropolitan Zone. Karapakkam is a rapidly developing hub along the bustling Old Mahabalipuram Road (OMR), characterized by significant IT, industrial, and commercial activity. Its strategic importance is further highlighted by its proximity to major neighborhoods like Sholinganallur, Thoraipakkam, Pallikaranai, and Injambakkam. A primary survey, including a detailed analysis of comprehensive land use and land cover (LULC), reveals that the area is predominantly residential, with additional insights derived from the distribution of building ages. Analysis of how information technology and industrial blooms like micro- and macro-industries affect the residential zone and urban sustainable pattern of Karapakkam. During the transition, agricultural areas have vanished. Karapakkam features a variety of water bodies, with Okkiyam Maduvu standing as the largest river contributing to its hydrological diversity. Commercial sectors are primarily concentrated along state highway 49A (SH 49A), and with anticipated growth in these areas, encouraging mixed-use development can integrate multiple functions within a single building, enhancing urban sustainability. By using the SWAT model, the surface runoff can be simulated, and peak runoff is calculated by the rational method to develop mitigation strategies.
Keywords: SWAT model; Urban resilience; disaster risk; peak runoff; rational method